Mortality in patients with TIMI 3 flow after PCI in relation to time delay to reperfusion - Vichova, Teodora; Maly, Marek; Ulman, Jaroslav; Motovska, Zuzana (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
BACKGROUND: Percutaneous coronary intervention (PCI) performed within 12 h from symptom onset enables complete blood flow restoration in infarct-related artery in 90% of patients. Nevertheless, even with complete restoration of epicardial blood flow in culprit vessel (postprocedural Thrombolysis in Myocardial Infarction (TIMI) flow grade 3), myocardial perfusion at tissue level may be insufficient. We hypothesized that the outcome of patients with STEMI/bundle branch block (BBB)-myocardial infarction and post-PCI TIMI 3 flow is related to the time to reperfusion. METHODS: Observational study based on a retrospective analysis of population of 635 consecutive patients with STEMI/BBB-MI and post-PCI TIMI 3 flow from January 2009 to December 2011 (mean age 63 years, 69.6% males). Mortality of patients was evaluated in relation to the time from symptom onset to reperfusion. RESULTS: A total of 83 patients (13.07%) with postprocedural TIMI 3 flow after PCI had died at 1-year follow-up. Median TD in patients who survived was 3.92 h (iqr 5.43), in patients who died 6.0 h (iqr 11.42), P = 0.004. Multiple logistic regression analysis identified time delay ≥ 9 h as significantly related to 1-year mortality of patients with STEMI/BBB-MI and post-PCI TIMI 3 flow (OR 1.958, P = 0.026). Other significant variables associated with mortality in multivariate regression analysis were: left ventricle ejection fraction < 30% (P = 0.006), age > 65 years (P < 0.001), Killip class >2 (P <0.001), female gender (P = 0.019), and creatinine clearance < 30 mL/min (P < 0.001). CONCLUSION: Time delay to reperfusion is significantly related to 1-year mortality of patients with STEMI/BBB-MI and complete restoration of epicardial blood flow in culprit vessel after PCI.
Keywords: senioři; TIMI 3 flow; Retrospective Studies; Myocardial Reperfusion; Česká republika; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; infarkt myokardu; Kaplanův-Meierův odhad; Czech Republic; Microcirculation; Postoperative Complications; time-delay; Myocardial Infarction; microcirculation; ženské pohlaví; Time-to-Treatment; retrospektivní studie; Bundle-Branch Block; Humans; koronární stenóza; koronární angioplastika; reperfuze myokardu; lidé středního věku; Percutaneous Coronary Intervention; STE myocardial infarction; blokáda Tawarova raménka; PCI; Coronary Stenosis; Female; mikrocirkulace; Aged; čas zasáhnout při rozvinutí nemoci; mortality; pooperační komplikace; lidé; Male